Anthropogenic disturbances simplify frugivory interactions in Amazonia - Rossi, Liana Chesini [UNESP]; Emer, Carine [UNESP]; Lees, Alexander Charles; Berenguer, Erika; Barlow, Jos; Ferreira, Joice; França, Filipe M.; Ramos, Yan Gabriel; Tavares, Paulo; Pizo, Marco Aurelio [UNESP] (Wiley, 2025)
Frugivory interactions are essential ecological processes for the regeneration of tropical forests, ensuring ecosystem resilience following disturbances. However, little is known about how frugivory interactions are shaped by anthropogenic disturbances, especially in Amazonia – one of the most biodiverse ecosystems on Earth. We investigate how selective logging and forest fires impact both arboreal and terrestrial frugivory interactions in Amazonian forests. We focus on four forest classes: Undisturbed, Logged, Logged‐and‐17y‐burned (burned 17 years before sampling) and Logged‐and‐3y‐burned (burned three years before sampling). We recorded 4670 frugivory interactions at the community level, in a sampling effort of 31 484 h. Undisturbed forests sustained a significantly higher number of species and interactions when compared to Logged‐and‐17y‐burned forests, and similar numbers to Logged and Logged‐and‐3y‐burned. Selective logging and forest fires did not alter significantly the structural properties of the frugivory networks, which were highly modular, moderately specialised, poorly connected and non‐nested. Regarding community composition, we detected high β‐diversity of plant species, frugivore species, and their interactions between all study areas, as well as within and between forest classes, mainly driven by species turnover. Logged‐and‐17y‐burned forests hosted the most unique interaction composition compared to Undisturbed forests. Our study provides novel evidence that anthropogenic disturbances, particularly selective logging and forest fires, negatively affect frugivory interactions in Amazonian forests. These effects may persist for years after the initial disturbance events and could be exacerbated due to the predicted increase in forest fires driven by climate change.